The Micronecta Kirkaldy, 1897 (Hemiptera: Heteroptera: Micronectidae) of Iran, with four new records and an illustrated key to the species - Rajabian, Mona; Hosseini, Reza (Zootaxa, 2023)
The fauna of Micronectidae (pygmy water boatmen) was investigated in Guilan Province. The present study has raised the number of micronectid species known from Iran to nine by reporting four first records for the country, including Micronecta carpatica Wróblewski, 1958, M. griseola Horváth, 1899, M. poweri (Douglas & Scott, 1869), and M. pusilla (Horváth, 1895). Morphological diagnoses for these four species are provided, accompanied by illustrations of male habitus, male genitalia, and a key to the species of Micronecta known from Iran.